A Clinical Prospective Observational Cohort Study on the Prevalence and Primary Diagnostic Accuracy of Occult Vertebral Fractures in Aged Women with Acute Lower Back Pain Using Magnetic Resonance Imaging. (25th May 2017) - Terakado, Atsushi; Orita, Sumihisa; Inage, Kazuhide; Kubota, Go; Kanzaki, Tomohiro; Mori, Hiroshi; Shinohara, Yuji; Nakamura, Junichi; Matsuura, Yusuke; Aoki, Yasuchika; Furuya, Takeo; Koda, Masao; et al.
Abstract : Background. Elderly female patients complaints of acute low back pain (LBP) may involve vertebral fracture (VF), among which occult VF (OVF: early-stage VF without any morphological change) is often missed to be detected by primary X-ray examination. The current study aimed to investigate the prevalence of VF and OVF and the diagnostic accuracy of the initial X-ray in detecting OVF. Method. Subjects were elderly women (>70 years old) complaining of acute LBP with an accurate onset date. Subjects underwent lumbar X-ray, magnetic resonance imaging (MRI), and bone mineral density (BMD) measurement at their first visit. The distribution of radiological findings from X-ray and magnetic resonance imaging (MRI) as well as the calculation of the prevalence of VF and OVF are investigated. Results . The prevalence of VF among elderly women with LBP was 76.5% and L1 was the most commonly injured level. Among VF cases, the prevalence of OVF was 33.3%. Furthermore, osteoporotic patients tend to show increased prevalence of VF (87.5%). The predictive values in detecting VF on the initial plain X-ray were as follows: sensitivity, 51.3%; specificity, 75.0%; and accuracy rate, 56.7%. Conclusions. Acute LBP patients may suffer vertebral injury with almost no morphologic change in X-ray, which can be detected using MRI.